Consumers' intentions and behaviour: A note on research and a challenge to researchers - Foxall, Gordon R. (Cranfield School of Management, 1983)
This paper examines the widespread attempts of market researchers to predict aspects of consumer choice on the basis of survey respondents' verbally-expressed intentions to buy. In particular, it assesses the Fishbein behavioural intentions model which represents the most sophisticated technique available for such work. Theoretical, experimental and practical evidence is advanced to demonstrate the futility of employing models which assume linear continuity between intentions an behaviour in the predications of many managerially-relevant aspects of consumer behaviour,notably brand choice. the major purpose of the paper is the identification of an important source of weakness in theassumptions which underpin current market research practice. the concluding section draws attention to the need for viable altenatives.